Accuracy and reproducibility of assessing right ventricular function with 64-section multi-detector row CT: Comparison with magnetic resonance imaging - Guo, Ying-kun; Gao, Hong-ling; Zhang, Xiao-chun; Wang, Qi-ling; Yang, Zhi-gang; Ma, En-sen (International journal of cardiology, 2010)
Right ventricular (RV) function is very important for those patients with respiratory and cardiovascular disorders that can result in RV impairments. Because of complex geometry of the chamber, it is difficult to accurately measure the RV volumetric parameters with conventional imaging modalities. The purpose of this study was to evaluate whether the 64-MDCT can assess RV function with high accuracy and reproducibility when compared to the results with those of MRI. Forty-seven consecutive subjects underwent retrospectively ECG-gated 64-MDCT and MRI for assessing the ventricular function. Right ventricular end diastolic and end-systolic volume, stroke volume, and ejection fraction were measured with dedicated cardiac analysis software on 64-MDCT and compared with values measured on MRI which served as the reference standard. Agreement between two modalities was assessed with Bland and Altman analysis and linear regression analysis. Repeated measurements were performed to determine intraobserver and interobserver variability. No significant differences were revealed in calculated RV volumes and EF between the two modalities. Agreement and correlation were similar for RV–EDV (0.4±8.2 ml; r=0.95), RV–ESV (−0.6±4.8; r=0.95), RV–SV (1.1±6.7 ml; r=0.93), and RV–EF (0.9±4.4; r=0.88). The difference of SV of right and left ventricle with 64-MDCT was not statistically significant (p=0.40) and good correlation was obtained (r=0.96). The variability in 64-MDCT measurements was lower than those in MRI. ECG-gated 64-MDCT can assess the RV function with high accuracy and reproducibility without geometric assumptions about right ventricle.